Analysis of the Basics and Foundations of Islamic Religious Education Curriculum Development Interdisciplinary, Multidisciplinary and Transdisciplinary Approaches - Asmiatin, Asmiatin; Fattahuddin, M.; Khoiri, Khoiri; Darmawati, Darmawati; S, Munawir; Djollong, Andi Fitriani (PT. Anagata Sembagi Education, 2025)
This article aims to analyze the basics and foundations of the development of the Islamic Religious Education (PAI) curriculum with an interdisciplinary, multidisciplinary, and transdisciplinary approach in response to the complexity of 21st century educational challenges. The PAI curriculum is required not only to teach religious aspects normatively, but also to equip students with the ability to think critically, reflectively, and contextually in dealing with social realities. A multidisciplinary approach plays a role in enriching teaching materials through the contribution of various sciences without removing interdisciplinary boundaries. Meanwhile, an interdisciplinary approach allows collaboration between fields of science to produce a more in-depth scientific synthesis. The transdisciplinary approach actually breaks through disciplinary boundaries by focusing on solving real problems through an integrative and holistic perspective. This research uses a qualitative method with a library research approach. Data sources were obtained from scientific journals, books, and education policy documents published in the last five years. Data analysis was carried out in a descriptive analytical manner to identify the basic principles and theoretical foundations that are the basis in the development of the PAI curriculum with the three approaches. The results of the study show that the development of the PAI curriculum based on an inter-, multi-, and transdisciplinary approach contributes significantly to the creation of a learning system that is adaptive, contextual, and relevant to the needs of the times and supports the formation of religious and humanist character.